CRISPR/Cas9-Mediated Targeted Mutagenesis of FtMYB45 Promotes Flavonoid Biosynthesis in Tartary Buckwheat (Fagopyrum tataricum) - Wen, Dong; Wu, Lan; Wang, Mengyue; Yang, Wei; Wang, Xingwen; Ma, Wei; Sun, Wei; Chen, Shilin; Xiang, Li; Shi, Yuhua (Frontiers in Plant Science, 2022)
CRISPR/Cas9 technology has been proven to be an efficient genome editing tool and has been widely applied in multiple plant species. However, it has not been reported in tartary buckwheat (Fagopyrum tataricum), which is an important edible and medicinal crop rich in rutin and other flavonoids. FtMYB45 is an R2R3-type MYB transcription factor and acts as a negative regulator in flavonoids biosynthesis in tartary buckwheat. Here, the CRISPR/Cas9 system PTG/Cas9 was employed to knock out the FtMYB45 gene in tartary buckwheat. Two target single-guide RNAs (sgRNAs) were designed in the second exon of FtMYB45 gene. Twelve transformed hairy roots were obtained by Agrobacterium rhizogenes mediated transformation. Sequencing results revealed that six lines containing six types of mutations at the predicted double-stranded break site of sgRNA1 were generated, and the mutation frequency reached 50%. The LC-QqQ-MS based metabolomic analysis indicated that the content of rutin, catechin and other flavonoids were increased in mutant hairy roots compared with those in empty vector transgenic lines. Thus, CRISPR/Cas9-mediated targeted mutagenesis FtMYB45 can effectively increase the content of flavonoids in tartary buckwheat. The founding demonstrated that CRISPR/Cas9 is an efficient tool for precise genome editing in tartary buckwheat and will lay an important foundation for gene function research and quality improvement in tartary buckwheat.